Involvement Patterns of Pentahelix Elements in Tourism Village Development - Andre Ariesmansyah; Rifqi Khairul Arifin (Khazanah Multidisiplin, 2025)
The development of tourism villages in Patengan Village, Rancabali District, has attracted the attention of many parties. Although many promotional activities have been carried out, the tourism potential of Patengan Village is still not optimally utilized and requires improvements in area management. This research aims to deeply explain the phenomenon of the involvement patterns of Penta-helix elements in the development of Patengan tourism village. This research adopts a descriptive design with a qualitative approach, located in Patengan Village, and uses the theory of Halibas et al. Data collection was carried out through interviews, observation, and documentation, with source triangulation to verify data validity. Data analysis used the interactive model of Miles and Huberman. Initial observations from the Focus Group Discussion (FGD) in Patengan Village, involving village government stakeholders, the community, and businesses, showed that tourism village development has not been optimal due to the minimal involvement of multi-parties (Penta-helix). Challenges include inadequate infrastructure, limited understanding of human resources among village officials and BUMDES (Village-Owned Enterprises), lack of understanding of cross-sector collaboration, limited promotion, minimal involvement of communities and academics, and lack of support from the business world. Other crucial factors are the lack of trust among collaborating parties, as well as budget and human resource limitations. This research is expected to provide an overview of the Penta-helix involvement patterns and identify inhibiting factors, which will form the basis for formulating targeted solutions for the sustainable development of tourism villages.